Exceptional and Durable Responses to TDM-1 After Trastuzumab Failure for Breast Cancer Skin Metastases: Potential Implications of an Immunological Sanctuary - Giarratano, Tommaso; Miglietta, Federica; Giorgi, Carlo A.; Tsvetkova, Vassilena; Michieletto, Silvia; Evangelista, Laura; Polico, Ilaria; Dieci, Maria V.; Guarneri, Valentina (Frontiers in Oncology, 2018)
Breast Cancer (BC) skin metastases represent a challenging clinical scenario. Although they usually arise when other distant metastases are already present, they may also represent a form of locoregional recurrence (LRR). Systemic therapy in this setting may have a role both in case a radical locoregional approach is unfeasible in order to achieve disease control, and as adjuvant strategy after radical removal of cutaneous lesions, in order to prevent or delay subsequent disease spread. Systemic therapy for HER2+ metastatic BC (MBC) currently relies on anti-HER2 targeted agents. In this context TDM1 is an option in trastuzumab-resistant patients. Here we present 2 cases of isolated skin metastases in patients with HER2+ BC progressing during or early after trastuzumab-based therapy, showing impressive responses to TDM1. We hypothesize that the unique properties of skin immune microenvironment may explain the failure of trastuzumab, which exerts its action mainly through immunological mechanisms, and the subsequent outlier responses to TDM1, that relies on a partially different mechanism of action.